Epidemiology and outcome predictors in 450 patients with hanging-induced cardiac arrest: a retrospective study - Salvetti, Marie; Schnell, Guillaume; Pichon, Nicolas; Schenck, Maleka; Cronier, Pierrick; Perbet, Sebastien; Lascarrou, Jean-Baptiste; Guitton, Christophe; Lesieur, Olivier; Argaud, Laurent; Colin, Gwenhael; Cholley, Bernard; et al. (Frontiers in Neurology, 2023)
Background Cardiac arrest is the most life-threatening complication of attempted suicide by hanging. However, data are scarce on its characteristics and outcome predictors. Methods This retrospective observational multicentre study in 31 hospitals included consecutive adults admitted after cardiac arrest induced by suicidal hanging. Factors associated with in-hospital mortality were identified by multivariate logistic regression with multiple imputations for missing data and adjusted to the temporal trends over the study period. Results Of 450 patients (350 men, median age, 43 [34–52] years), 305 (68%) had a psychiatric history, and 31 (6.9%) attempted hanging while hospitalized. The median time from unhanging to cardiopulmonary resuscitation was 0 [0–5] min, and the median time to return of spontaneous circulation (ROSC) was 20 [10–30] min. Seventy-nine (18%) patients survived to hospital discharge. Three variables were independently associated with higher in-hospital mortality: time from collapse or unhanging to ROSC>20 min (odds ratio [OR], 4.71; 95% confidence intervals [95%CIs], 2.02–10.96; p = 0.0004); glycaemia >1.4 g/L at admission (OR, 6.38; 95%CI, 2.60–15.66; p < 0.0001); and lactate >3.5 mmol/L at admission (OR, 6.08; 95%CI, 1.71–21.06; p = 0.005). A Glasgow Coma Scale (GCS) score of >5 at admission was associated with lower in-hospital mortality (OR, 0.009; 95%CI, 0.02–0.37; p = 0.0009). Conclusion In patients with hanging-induced cardiac arrest, time from collapse or unhanging to return of spontaneous circulation, glycaemia, arterial lactate, and coma depth at admission were independently associated with survival to hospital discharge. Knowledge of these risk factors may help guide treatment decisions in these patients at high risk of hospital mortality.